A materialidade do ICMS-Importação e a Emenda Constitucional nº 33 de 2001 - Vanni, Leonardo (2014)
This paper intends to investigate into the effects related to the insertion proposed by Constitutional Amendment No. 33 of 2001, which we understand to have created a new tax exaction similar to import duty, but to be imposed by the States and the Federal District. In this sense, we seek to understand the views of the more modern doctrine on the matter, in order to be equipped with instruments capable of understanding the appropriateness of the amendment to the current constitutional context. Research on screen starts with the details of tax on merchandise operations (ICMS), in relation with the incidence of this same tax on import operations (ICMSImportação) with merchandise. At this point, we will hold that the incident on the import of goods does not constitute an autonomous state tax tax species and should bear consistency with the materiality of the tax levied on domestic operations (ICMS). Following the same lines, the study in question will reach it´s goal entering specifically into the changes performed by that Constitutional amendment in order to demonstrate the "extension" of the taxing power of the states and the Federal District, made by the constitutional legislator derived, hurting taxpayer individual guarantee, thus being unconstitutional under item IV, § 4, Article 60 of the present Federal Constitution. Finally, we will investigate the emblematic cases involving the particularities of change promoted by Constitutional Amendment No. 33, 2001, in accordance with the concepts learned in previous chapters, firming opinion about the cases analyzed